Pengelolaan Pembelajaran Pendidikan Agama Islam pada Masa Rasulullah dan Masa Modern - Aulia, Elsa Lady; Fahruddin, Fahruddin (TA'LIMUNA: Jurnal Pendidikan Islam, 2022)
Abstract: The purpose of this study is to identify how to analyze Islamic learning management during the time of the Prophet Muhammad, to identify how to analyze Islamic learning management in the modern era, and to identify comparative analysis of Islamic learning management at the time of the Prophet Muhammad. SAW as well as in this modern era. Based on the results of the research, it can be seen that from the author's analysis of the management of Islamic learning at the time of the Prophet Muhammad, it can be concluded from planning that has a fundamental character for the learning objectives of these friends and the people only. It is a moral medicine, and it is a learning vision. inside it. Organizing, at the time of the Prophet Muhammad SAW, the organization that became Dicala's strength was the mandate and enthusiasm in carrying out the mandate given to his friends (application), at the time of Rasulullah SAW, the application was tried in the learning process was a reliable effort and effort without neighing supervision (supervision) during the supervision of the Messenger of Allah. Keywords: management, Islamic learning, Rasulullah SAW era, modern era. Abstrak: Tujuan dari penelitian ini adalah untuk mengidentifikasi bagaimana menganalisis manajemen pembelajaran Islam pada masa Nabi Muhammad, untuk mengidentifikasi bagaimana menganalisis manajemen pembelajaran Islam di era modern, dan untuk mengidentifikasi analisis komparatif manajemen pembelajaran Islam pada masa Nabi. Muhammad. SAW maupun di era modern ini. Berdasarkan hasil penelitian dapat diketahui bahwa dari analisis penulis tentang pengelolaan pembelajaran Islam pada masa Nabi Muhammad SAW, dapat disimpulkan dari perencanaan yang bersifat fundamental untuk tujuan pembelajaran para sahabat ini dan orang-orangnya saja. Ini adalah obat moral, dan itu adalah visi pembelajaran. di dalamnya. Berorganisasi Pada masa Nabi Muhammad SAW, organisasi yang menjadi kekuatan Dicala adalah amanah dan semangat dalam menjalankan amanah yang diberikan kepada para sahabat (aplikasi), pada masa Rasulullah SAW aplikasi dicoba dalam proses pembelajaran. merupakan ikhtiar dan ikhtiar yang dapat diandalkan tanpa harus melingkupi pengawasan (pengawasan) selama pengawasan Rasulullah. Kata Kunci: pengelolaan, pembelajaran PAI, masa Rasulullah, masa modern